Web-based employee reward determination system using Analytical Hierarchy Process (AHP) - Maulana, Muhammad Fajar; Sumardiono, Sumardiono (Jurnal Simantec, 2025)
This study develops a web-based employee performance evaluation system using the Analytical Hierarchy Process (AHP) method to overcome the problem of inaccuracy and unfairness in reward giving at PT Transcosmos Commerce. The system is designed using an Agile approach with the Django framework and SQLite database. The AHP method is applied to calculate the weight of the assessment criteria (discipline, responsibility, productivity, work quality, and cooperation) through pairwise comparisons, resulting in a consistency ratio (CR) value of 0.08 less than 0.1, which indicates acceptable consistency. The results of the AHP calculation show that the highest criterion weight is Productivity (0.32), followed by Work Quality (0.25), Responsibility (0.18), Cooperation (0.15), and Discipline (0.10). The final employee score is obtained by combining the criteria weight and alternative values, with the highest scores obtained by employees A1 (Dani) of 0.42, A2 (Farhan) of 0.35, and A3 (Freya) of 0.23. System testing has proven an increase in evaluation time efficiency of 60 percent compared to manual methods, as well as reducing the subjectivity of assessments. The system also provides visualization of results in the form of graphs and automatic reports, facilitating managerial decision-making.Keywords: AHP, criteria weighting, evaluation of performence, employee reward, Web Based System.